Membangun Kesiapan Berubah dan Kinerja Karyawan: Kepemimpinan Transformasional versus Transaksional - Masduki Asbari; John Tampil Purba; Evo Sampetua Hariandja; Niko Sudibjo (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2021)
This study aims to measure the effect of transformational and transactional leadership on employee performance in the HVAC industry in Tangerang mediated by readiness for change. The data was collected by using simple random sampling technique and the results of the questionnaire that returned and were valid as many as 224 samples. Data processing using SEM method with SmartPLS 3.0 software. The results of this study concluded that transformational leadership has a significant effect on employee performance and readiness to change. In contrast to transactional leadership which does not have a significant effect on both performance and readiness to change. This study also concludes that readiness to change has a positive and significant effect on the relationship between transformational leadership and employee performance. This new research proposes a model for building employee performance among employees of the HVAC industry in Tangerang through enhancing transformational leadership practices with readiness to change as a mediator. This research can pave the way to improve employee readiness in the face of the industrial revolution 4.0 era.